Determinants of Indonesian people attitudes towards people living with HIV/AIDS (PLWHA) - Rini Mutahar (Universiti Kebangsaan Malaysia, 2011)
Negative attitudes toward people with HIV/AIDS (PLWHA) can occur from various groups. Negative attitude from the community can affect the psychological condition of people living with HIV. In addition, the reduction of stigma and discrimination in society is an important indicator to measure the success of prevention programs of HIV/AIDS. The objective of the study was to determine the factors associated with the Indonesian people towards PLWHA.